Kajian rintis ke atas sikap pengguna bukan islam terhadap produk makanan halal / Dayang Haryani Diana Ag. Damit, Amran Harun and Halim Ahmad - Ag. Damit, Dayang Haryani Diana; Harun, Amran; Ahmad, Halim (Universiti Teknologi MARA, Sabah, 2017)
This pilot study aimed to assess factors such as consumer’s lifestyle, consumer perception of product quality and past purchase experiences that can influence non-Muslims consumer attitudes toward Halal food products. Using random sampling method, a total of 134 respondents consisted non-Muslim consumers from around Kota Kinabalu were selected for this study. The survey questionnaire include 17 items and distributed to the respondents. Statistical Package for Social Science (SPSS) version 20.0 was used to analyze the data. Additionaly, SmartPLS 3.0 was also utilized in this pilot study in order to perform construct validity analysis and hypothesis testing. At the end of this article, the researchers suggest several conclusions and recommendation for future research.